Dukungan Kepemimpinan Mutu Perguruan Tinggi Dalam Penerapan Manajemen Mutu Terpadu (MMT): Studi Kasus pada STAIN Watampone - Bakar, H Abu (Al-Riwayah : Jurnal Kependidikan, 2015)
Fourteen points of Deming’s thought about increasing the quality of the educational menagement are epected to be implemented in improving educational management quality in Indonesia. It is said that the essence of thing about the Deming’s concept is leadership. Casmpus STAIN Watampone, as a social institution, is expected to meet the needs of the community about quality education. Principals have an important role in implementing integrated quality or TQM in Campus. STAIN Watampone in a school will not run properly if it is not supported by quality-oriented leadership behavior of the principals. The focus of this research is the problem in leadership behaviors of school principals in implementing STAIN Watampone. This study has the objectives to determine the commitment of the school. The behavior of the principal’s leadership is improving the quality, and strategic leadership in improving the quality.